Long-term follow-up of Helicobacter pylori reinfection and its risk factors after initial eradication: a large-scale multicentre, prospective open cohort, observational study - Yong Xie; Conghua Song; Hong Cheng; Canxia Xu; Zhenyu Zhang; Jiangbin Wang; Lijuan Huo; Qin Du; Jianming Xu; Ye Chen; Xiaomei Zhang; Guoxin Zhang; et al. (Emerging Microbes and Infections)
Helicobacter pylori (H. pylori) recurrence remains a significant public health concern. The study aimed to assess H. pylori reinfection rate and identify its risk factors in China. This prospective open cohort, observational study was performed at 18 hospitals across 15 provinces in China. Consecutive patients who received the successful initial eradication during 1 January 2012 and 31 December 2018 were eligible for enrolment. H. pylori recurrence was defined as reinfection that occurred at more than the 12-month interval after successful initial eradication. Surveyed risk factors that might be associated with reinfection were preliminarily estimated by log-rank test and further determined by Cox regression model to calculate the hazard ratio (HR) and 95% confidence interval (CI). A total of 5193 subjects enrolled in the study. The follow-up intervals varied from 6 to 84 months with a general follow-up rate of 67.9%. Annual reinfection rate was 1.5% (95% CI: 1.2–1.8) per person-year. H. pylori reinfection was independently associated with the following five risk factors: minority groups (HR = 4.7, 95% CI: 1.6–13.9), the education at lower levels (HR = 1.7, 95% CI: 1.1–2.6), a family history of gastric cancer (HR = 9.9, 95% CI: 6.6–14.7), and the residence located in Western China (HR = 5.5, 95% CI: 2.6–11.5) following by in Central China (HR = 4.9, 95% CI: 3–8.1) (all P < 0.05). Reinfection rate of H. pylori in China is relatively low. Patients with specific properties of ethnic groups, education level, family history, or residence location appear to be at higher risk for reinfection.